Association of CTLA-4 Gene Variants with Response to Therapy and Long-term Survival in Metastatic Melanoma Patients Treated with Ipilimumab: An Italian Melanoma Intergroup Study - Queirolo, Paola; Dozin, Beatrice; Morabito, Anna; Banelli, Barbara; Piccioli, Patrizia; Fava, Cristiana; Leo, Claudio; Carosio, Roberta; Laurent, Stefania; Fontana, Vincenzo; Ferrucci, Pier Francesco; Martinoli, Chiara; et al. (Frontiers in Immunology, 2017)
Ipilimumab (IPI) blocks CTLA-4 immune checkpoint resulting in T cell activation and enhanced antitumor immunity. IPI improves overall survival (OS) in 22% of patients with metastatic melanoma (MM). We investigated the association of CTLA-4 single nucleotide variants (SNVs) with best overall response (BOR) to IPI and OS in a cohort of 173 MM patients. Patients were genotyped for six CTLA-4 SNVs (-1661A>G, -1577G>A, -658C>T, -319C>T, +49A>G and CT60G>A). We assessed the association between SNVs and BOR through multinomial logistic regression (MLR) and the prognostic effect of SNVs on OS through Kaplan-Meier method. Both -1577G>A and CT60G>A SNVs were found significantly associated with BOR. In particular, the proportion of responders was higher in G/G genotype while that of stable patients was higher in A/A genotype. The frequency of patients experiencing progression was similar in all genotypes. MLR evidenced a strong downward trend in the probability of responsiveness/progression, in comparison to disease stability, as a function of the allele A “dose” (0, 1 or 2) in both SNVs with reductions of about 70% (G/A vs G/G) and about 95% (A/A vs G/G). Moreover, -1577G/G and CT60G/G genotypes were associated with long-term OS, the surviving patients being at 3-years 29.8% and 30.8%, respectively, as compared to 12.9% and 14.4% of surviving patients carrying -1577G/A and CT60G/A, respectively. MM patients carrying -1577G/G or CT60G/G genotypes may benefit from IPI treatment in terms of BOR and long-term OS. These CTLA-4 SNVs may serve as potential biomarkers predictive of favorable outcome in this subset of patients.